Functional characterization and transient expression manipulation of a new sesquiterpene synthase involved in beta-caryophyllene accumulation in Ocimum - Jayaramaiah, Ramesha H.; Anand, Atul; Beedkar, Supriya D.; Dholakia, Shushan B.; Punekar, Sachin A.; Kalunke, Raviraj M.; Gade, Wasudeo N.; Thulasiram, Hirekodathakallu V.; Giri, Ashok P. (Biochemical And Biophysical Research Communications, 2016)
The genus Ocimum has a unique blend of diverse secondary metabolites, with major proportion of terpenoids including mono- and sesquiterpenes. Although, beta-Caryophyllene, bicyclic sesquiterpene, is one of the major terpene found in Ocimum species and known to possess several biological activities, not much is known about its biosynthesis in Ocimum. Here, we describe isolation and characterization of beta-caryophyllene synthase gene from Ocimum kilimandscharicum Gurke (OkBCS- GenBank accession no. KP226502). The open reading frame of 1629 bp encoded a protein of 542 amino acids with molecular mass of 63.6 kDa and pl value of 5.66. The deduced amino acid sequence revealed 50-70% similarity with known sesquiterpene synthases from angiosperms. Recombinant OkBCS converted farnesyl diphosphate to beta-caryophyllene as a major product (94%) and 6% alpha-humulene. Expression variation of OkBCS well corroborated with beta-caryophyllene levels in different tissues from five Ocimum species. OkBCS transcript revealed higher expression in leaves and flowers. Further, agro-infiltration based transient expression manipulation with OkBCS over-expression and silencing confirmed its role in beta-caryophyllene biosynthesis. These findings may potentially be further utilized to improve plant defense against insect pests. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: beta-Caryophyllene; Natural product biosynthesis; Ocimum; Terpene synthase; Transient expression

Fusarium oxysporum mediates systems metabolic reprogramming of chickpea roots as revealed by a combination of proteomics and metabolomics - Kumar, Yashwant; Zhang, Limin; Panigrahi, Priyabrata; Dholakia, Bhushan B.; Dewangan, Veena; Chavan, Sachin G.; Kunjir, Shrikant M.; Wu, Xiangyu; Li, Ning; Rajmohanan, Pattuparambil R.; Kadoo, Narendra Y.; Giri, Ashok P.; et al. (Plant Biotechnology Journal, 2016)
Molecular changes elicited by plants in response to fungal attack and how this affects plant-pathogen interaction, including susceptibility or resistance, remain elusive. We studied the dynamics in root metabolism during compatible and incompatible interactions between chickpea and Fusarium oxysporum f. sp. ciceri (Foc), using quantitative label-free proteomics and NMR-based metabolomics. Results demonstrated differential expression of proteins and metabolites upon Foc inoculations in the resistant plants compared with the susceptible ones. Additionally, expression analysis of candidate genes supported the proteomic and metabolic variations in the chickpea roots upon Foc inoculation. In particular, we found that the resistant plants revealed significant increase in the carbon and nitrogen metabolism; generation of reactive oxygen species (ROS), lignification and phytoalexins. The levels of some of the pathogenesis-related proteins were significantly higher upon Foc inoculation in the resistant plant. Interestingly, results also exhibited the crucial role of altered Yang cycle, which contributed in different methylation reactions and unfolded protein response in the chickpea roots against Foc. Overall, the observed modulations in the metabolic flux as outcome of several orchestrated molecular events are determinant of plant's role in chickpea-Foc interactions.
Keywords: Chickpea; fusarium oxysporum; Metabolomics; NMR; plant-pathogen interaction; proteomics

Functional insights into two Ocimum kilimandscharicum 4-coumarate-CoA ligases involved in phenylpropanoid biosynthesis - Lavhale, Santosh G.; Joshi, Rakesh S.; Kumar, Yashwant; Giri, Ashok P. (International Journal of Biological Macromolecules, 2021)
Plant 4-coumarate-CoA ligase (4CL) catalyzes the ligation of CoA to cinnamic acid and its derivatives. Activated CoA esters are utilized for the biosynthesis of phenolic metabolites and lignin that play essential function in plants. Here, we characterize the diversity of Ocimum kilimandscharicum 4CLs (Ok4CLs). Phylogenetic analysis suggest that Ok4CLs could be grouped into three classes, class I -enzymes mostly involved in lignin biosynthesis, class II -non-structural phenylpropanoid biosynthesis and class III -yet to be characterized for specific role(s). We selected two Ok4CLs namely Ok4CL7 and Ok4CL15 for further characterization. Gene expression analysis sug-gested that Ok4CL7 is highly expressed in leaf trichomes, whereas Ok4CL15 is abundant in the roots. The recom-binant Ok4CL7 and Ok4CL15 had optimal enzyme activities at 40 degrees C in pH 8 and 7, respectively. Ok4CL7 showed substrate preference towards p-coumaric acid, ferulic acid and caffeic acid. While, Ok4CL15 preferredp-coumaric acid, ferulic acid and sinapic acid. Feruloyl adenylate showed higher number of contacts and lowers binding en-ergy with Ok4CL7 and 15 compared to cinnamoyl adenylate. Based on root-specific expression and preference for sinapic acid, Ok4CL15 might be involved in lignin biosynthesis. Further exploration is needed to unravel the role of diverse Ok4CLs in O. kilimandscharicum. (c) 2021 Elsevier B.V. All rights reserved.
Keywords: 4-Coumarate-CoA ligase; Flavonoids; lignin; Ocimum kilimandscharicum; Phenylpropanoids

Functional diversity of the lepidopteran ATP-binding cassette transporters - Barve, Pranoti R.; Tellis, Meenakshi B.; Barvkar, Vitthal T.; Joshi, Rakesh S.; Giri, Ashok P.; Kotkar, Hemlata M. (Journal of Molecular Evolution, 2022)
The ATP-binding cassette (ABC) transporter gene family is ubiquitous in the living world. ABC proteins bind and hydrolyze ATP to transport a myriad of molecules across various lipid-containing membrane systems. They have been studied well in plants for transport of a variety of compounds and particularly, in vertebrates due to their direct involvement in resistance mechanisms against several toxic molecules/metabolites. ABC transporters in insects are found within large multigene families involved in the efflux of chemical insecticides and toxic/undesired metabolites originating from food and endogenous metabolism. This review deals with ABC transporter subfamilies of few agronomically important Lepidopteran pests. The transcriptional dynamics and regulation of ABC transporters during insect development emphasizes their functional diversity against insecticides, Cry toxins, and plant specialized metabolites. To generate insights about molecular function and physiological roles of ABCs, functional and structural characterization is necessary. Also, expansion and divergence of ABC transporter gene subfamilies in Lepidopteran insects needs more systematic investigation. We anticipate that newer methods of insect control in agriculture can benefit from an understanding of ABC transporter interactions with a vast range of natural specialized molecules and synthetic compounds.
Keywords: ABC transporters; Bt; insecticide resistance; Lepidoptera; Plant metabolites